Efektywność wykorzystania majątku a wyniki ekonomiczne gospodarstw indywidualnych - Wasilewski, Mirosław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2005)
The aim of the paper was to analyze economic and financial outputs in relation to profitability of assets. In the group of farms with the highest profitability of assets, the highest level of land profitability, economic work efficiency and profitability of equity was observed. Farms with average or the highest level of assets profitability were also these with the highest accounting liquidity. The period of stocks turnover was the shortest in farms with the highest asset profitability. Comparing with other sectors, the period of stocks turnover was relatively long. The level of liabilities in farms was low. The managers of analyzed farms preferred prudent financial policy.